Stabilization of peat by cement-sodium silicate grout using injection-vacuum technology - Kazemian, Sina (2011)
Peat is a naturally occurring unconsolidated material; with high organic matter, high moisture content, and extremely soft in consistency. Due to its high compressibility and low shear strength, such soils are geotechnically problematic. The objective of this study was to stabilize peat, collected from different locations in Kampung Jawa, Selangor (West Malaysia), by using a new binder and adopting a new approach for mixing peat and binder i.e., a combination of injection and vacuum method. Grouting and chemical grouting technologies have grown over the last few decades. This study was carried out to investigate the influence of different amount of cement, sodium silicate, calcium chloride and kaolinite on the cement-sodium silicate grout with kaolinite for the stabilization of peat. The effectiveness of the grout was studied in terms of an increase in the shear strength of peat by performing vane shear test and a decrease in the moisture content of the samples after curing time. Scanning electron microscopy (SEM) and energy dispersive X-ray spectrometer (EDX) tests were performed to evaluate the microstructural changes taking place due to the interaction of peat and grouts. Calcium chloride seemed to have different effects on the shear strength of peat. Experimental results showed that kaolinite has crucial rule in increasing the shear strength of peat. It was observed that cement have favorable effects on the shear strength of peat and also lead to favorable changes in the microstructure. The rheology properties (viscosity, shrinkage, pH, and specific gravity) of the grouts were also examined. The effect of peat characteristics [CO2, Nitrogen (N), and pH] over time after treating with cement, cement-slag, and the new binder was evaluated. The mechanical properties of the samples were determined by performing unconfined compressive strength (UCS) test and the microstructure was studied by SEM. It was observed that the CO2 dissolved in peat water caused an increase in the depth of carbonation. The presence of an increasing amount of N had no tangible effect on cementation or pozzolanic reactions in the treated peats. Acidic media (pH) had a negative effect on cementation and pozzolanic reactions whereas the strength of peat treated with the new binder had no effect in the acidic media. In the concluding part of this study, the effect of the new binder on peat was evaluated by using the specially designed and fabricated deep mixing method (DMM) equipment. In this method, the new binder was injected in peat and a constant flow was achieved by a vacuum applied through a series of interconnected tubes installed in peat, which in turn were connected to a vacuum pump. The efficiency of this method was evaluated by studying the dispersion of grout. Due to the high permeability of peat, the binder could disperse homogeneously in peat with negative pressure. Finite element analysis was also carried out using the commercially available software (PLAXIS 2D v8.2) to study the effectiveness of the new DMM technique in comparison with conventional method i.e. injection method by using the results of the laboratory tests as input parameters.